The morphotropic phase boundary in the (1 - x)PbZrO3-x[0.3Bi(Zn1/2Ti1/2)O3-0.7PbTiO3] perovskite solid solution - Sareein T. (2014)
Ceramics in the (1 - x)PbZrO3-x[0.3Bi(Zn1/2Ti1/2)O3-0.7PbTiO3] solid solution system with 0.48 ≤ x ≤ 0.56 were investigated. A morphotropic phase boundary separating rhombohedral and tetragonal perovskite phases was identified at x = 0.52. This composition displays the maximum remanent polarization Pr of 40.7 μC/cm2 and the best piezoelectric coefficient d33 of 311 pC/N in the pseudo-binary system. However, the Curie temperature Tc for this MPB composition is 291 °C, much lower than initially expected. © 2011 Springer Science+Business Media, LLC.